Trends in the use of rehabilitation services in the community by people with mental disabilities in Israel; the factors involved - Hornik-Lurie Tzipi; Zilber Nelly; Lerner Yaacov (BMC, 2012)
Abstract Background In 2001, the Rehabilitation of the Mentally Disabled Law was implemented, defining a basket of rehabilitation services to which people with mental disabilities are entitled. Objectives To describe change over time in the characteristics of applicants to rehabilitation committees, types of referral agencies, and the proportion of those referred who were admitted. To identify factors affecting implementation of decisions to admit people with mental disabilities into different rehabilitation services and predictors of the length of time they remain in the services. Methods The study population consisted of all applicants to rehabilitation committees during 2001-2008. Rehabilitation services included hostels, supported housing, and vocational services. Data were extracted from Ministry of Health rehabilitation and psychiatric hospitalization case registers. Findings were analyzed using descriptive statistics, Kaplan-Meier survival analyses, and Cox regressions. Results There was a trend over time for more patients with shorter or no psychiatric hospitalization histories to be referred to rehabilitation services. Moreover, there was an increase in the proportion of referrals from the community, although the majority of referrals still came from psychiatric hospitals. Less than half of those recommended for a rehabilitation program were admitted and remained in a rehabilitation facility for one year or more. One factor predicting participants' longer stays in rehabilitation services after hospitalization was the proximity of the committees' decisions to the hospitalization. Another factor was the patient receiving vocational services while in residential care. Conclusion Although over time the new law has resulted in a broader spectrum of people with mental disabilities receiving rehabilitation services, additional efforts are needed to enable them to remain in the system for a sufficient amount of time. Programs addressing specific needs should be developed accordingly.